Copper‐Mediated Synthesis of Aryldifluoromethylphosphonates: A Sandmeyer Approach. Issue 17 (30th April 2015) - Bayle, Alexandre; Cocaud, Chloé; Nicolas, Cyril; Martin, Olivier R.; Poisson, Thomas; Pannecoucke, Xavier
Abstract: Difluoromethylated arenes are scaffolds of great interest. We report herein a mild and general method for the introduction of the CF2 PO(OEt)2 moiety into arenes. The CuCF2 PO(OEt)2 species, which is generated in situ from the corresponding silylated derivatives, in combination with aryl diazonium salts furnished the highly valuable aryl difluoromethylphosphonates in moderate to good yields. This represents the first general method to introduce difluoromethylphosphonates under mild conditions. Abstract : The valuable diethyl phosphonodifluoromethyl moiety was introduced into arenes by employing a Sandmeyer approach. This methodology represents a convenient alternative to the need for harsh reaction conditions or expensive starting materials.